The Italian Yearbook of International Law : Volume 13 (2003). - Conforti, Benedetto; Ferrari Bravo, L. (Luigi); Francioni, Francesco (BRILL, 2005)
The Italian Yearbook of International Law aims at making accessible to the English speaking public the Italian contribution to the practice and literature of international law. Volume XIII (2003) is organised in three main sections. The first contains doctrinal contributions including articles on State responsibility for the breach of positive obligations; State continuity and the case of Somalia; the European Union's international relations and the notion of fragmented sovereignty; self-defence and the problem of attribution of the September 11 attacks on the US; and the ICTY jurisprud.